2020
DOI: 10.3390/brainsci11010010
|View full text |Cite
|
Sign up to set email alerts
|

Network Analysis of Induced Neural Plasticity Post-Acceptance and Commitment Therapy for Chronic Pain

Abstract: Chronic musculoskeletal pain is a costly and prevalent condition that affects the lives of over 50 million individuals in the United States. Chronic pain leads to functional brain changes in those suffering from the condition. Not only does the primary pain network transform as the condition changes from acute to persistent pain, a state of hyper-connectivity also exists between the default mode, frontoparietal, and salience networks. Graph theory analysis has recently been used to investigate treatment-driven… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Recent literature has discovered that accelerated brain ageing accompanies chronic pain conditions, whereby lower cerebellar gray matter has been identified as a key pathological contributor [ 26 ]. Moreover, the aberrant neural functional activity of chronic pain conditions involves the activation of a multitude of brain areas, with cerebellar involvement being consistent with network changes associated with central sensitization [ 27 ]. Additionally, modernized findings explore further roles of the cerebellum in neuropsychiatric disorders [ 28 ] and serve to define a multitude of important physiological responses that require additional attention from researchers in the field of nociception and psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…Recent literature has discovered that accelerated brain ageing accompanies chronic pain conditions, whereby lower cerebellar gray matter has been identified as a key pathological contributor [ 26 ]. Moreover, the aberrant neural functional activity of chronic pain conditions involves the activation of a multitude of brain areas, with cerebellar involvement being consistent with network changes associated with central sensitization [ 27 ]. Additionally, modernized findings explore further roles of the cerebellum in neuropsychiatric disorders [ 28 ] and serve to define a multitude of important physiological responses that require additional attention from researchers in the field of nociception and psychiatry.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, while each network independently demonstrates changes in functional connectivity, it has also been reported that hyper-connectivity between these networks exists in patients with chronic pain ( Napadow et al, 2010 ; Hemington et al, 2018 ; van Ettinger-Veenstra et al, 2019 ; Ellingsen et al, 2021 ). Consistent with these findings, clinical studies have reported that pharmacological pain therapy reduced functional connectivity between DMN-SN and DMN-SMN ( Rogachov et al, 2019 ), and that cognitive-behavioral pain therapy reduced the functional connectivity between DMN, FPN, and SN in patients with chronic pain ( Meier et al, 2020 ). The neural oscillatory coupling between distant brain regions serves the integrative functions by facilitating information flow throughout the brain ( Fries, 2015 ).…”
Section: Future Direction Of Tacs Research For Pain Controlmentioning
confidence: 64%
“…Therefore, MBCT-induced modulation of pain is different from and relies on different mechanisms compared to placebo analgesia. Positive findings are also observed with ACT interventions in relation to pain, behavior and connectivity alterations across emotion, cognition and pain processing networks [161,162]. These novel findings provide key insights into the neural plasticity mechanisms by which cognitive therapies modulate central pain processing.…”
Section: Cognitive Therapymentioning
confidence: 69%